Industrial Relations Concepts in the USA - Barbash, Jack (Relations industrielles / Industrial Relations, 1991)
This paper is an effort at a synthesis of industrial relations concepts in the United States. Labor's human essence and employment equity are seen as the defining themes of industrial relations. The leading concepts are structured in a sort of logic or sequence of propositions which are summarily stated in the form of a syllabus as an expository device.